Functional analysis of a cinnamyl alcohol dehydrogenase involved in lignin biosynthesis in wheat - Ma, Qing-Hu (Oxford University Press, 2010)
Cinnamyl alcohol dehydrogenase (CAD) catalyses the final step in the biosynthesis of monolignols. In the present study, a cDNA encoding a CAD was isolated from wheat, designated as TaCAD1. A genome-wide data mining in the wheat EST database revealed another 10 CAD-like homologues, namely TaCAD2 to TaCAD11. A phylogenetic analysis showed that TaCAD1 belonged to the bona fide CAD group involved in lignin synthesis. Two other putative CADs from the wheat genome (TaCAD2 and TaCAD4) also belonged to this group and were very close to TaCAD1, but lacked C-terminal domain, suggesting that they are pseudogenes. DNA gel blot analysis for the wheat genome showed two to three copies of CAD related to TaCAD1, but RNA gel blot analysis revealed only single band for TaCAD1, which was highly expressed in stem, with quite low expression in leaf and undetectable expression in root. The predicted three-dimension structure of TaCAD1 resembled that of AtCAD5, but two amino acid substitutions were identified in the substrate binding region. Recombinant TaCAD1 protein used coniferyl aldehyde as the most favoured substrate, also showed high efficiencies toward sinapyl and p-coumaryl aldehydes. TaCAD1 was an enzyme being pH-dependent and temperature-sensitive, and showing a typical random catalysing mechanism. At the milky stage of wheat, TaCAD1 mRNA abundance, protein level and enzyme activity in stem tissues were higher in a lodging-resistant cultivar (H4546) than in lodging-sensitive cultivar (C6001). These properties were correlated to the lignin contents and lodging indices of the two cultivars. These data suggest that TaCAD1 is the predominant CAD in wheat stem for lignin biosynthesis and is critical for lodging resistance.